Acute and critical paediatric neurological conditions: The role of the neuroradiologist - Tang, Vicka; Kan, Yee Ling Elaine (The ASEAN Journal of Radiology, 2026)
Acute paediatric neurological diseases are common conditions that can result in significant morbidity and mortality, particularly if a timely diagnosis is not made. Unfortunately, clinical presentations can be non-specific, with seizures and headaches being the most frequent complaints. It is therefore important for radiologists to be familiar with these conditions and their respective imaging features to allow prompt diagnosis and management. <p style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The aim of this article is to briefly review the clinical presentation and imaging features across six common categories: intracranial haemorrhage, toxin-related injury, infections, autoimmune disorders, stroke, and seizures.